Industrial research institutes Guidelines for evaluation - United Nation; United Nation (Austria United Nation, 1971)
This book contains guidelines for evaluating economic growth which largely depends on industrial development.
ii, 14/01/2019
Loans
Keywords: Industrial research; Guideline; New York